Developing a Game-Enriched Guidebook for Museum Ganesya - Alvina Lwana Herman (UPT P2M Politeknik Negeri Malang, 2020)
The product result of the current study was an English game-enriched guidebook for Museum Ganesya. The guidebook was paper-based. The guidebook contained the museum’s rules, map, tour’s route, contact information, and also brief descriptions and photos on each section in the museum. A QR-code that would forward the users to the museum’s collections’ detailed descriptions was provided. A game called ‘Treasure Hunt’ was also provided in order to make the guidebook more interactive and attract younger generation interest. The game was a mission to search for answers to the questions related to the museum or the collections. The answers can be answered by writing down the answers on the provided crossword tiles or in Indonesian “kolom TTS.”